Stay Home, Stay Safe, Save Lives? An Analysis of the Impact of COVID-19 on the Ability of Victims of Gender-based Violence to Access Justice. (December 2020) - Speed, Ana; Thomson, Callum; Richardson, Kayliegh
On 23 March 2020, the United Kingdom (UK) government introduced new measures aimed at reducing the spread of coronavirus (Covid-19). These measures directed the closure of non-essential businesses and venues, prohibited all public gatherings of more than two people and required everyone to stay at home except for very limited purposes. The rationale behind the measures was clear: Stay Home, Stay Safe, Save Lives. Within days of the lockdown coming into force, reports emerged within the media that services supporting victims of gender-based violence (GBV) were facing an unprecedented increase in demand for assistance, indicating that cases of abuse were on the rise. Although GBV is not caused by lockdown measures, evidence indicates that they may increase the incidence rate and/or the severity of GBV in households where it is already being perpetrated. These findings are in line with existing research which demonstrates that natural disasters, disease and other forms of conflict leave citizens (particularly women and girls) vulnerable to GBV. Preventing and responding to GBV in times of humanitarian crises is a vital but challenging endeavour. Whilst support services struggle to secure adequate resources and capacity, restrictions on leaving the house mean that victims face barriers to reporting abuse and seeking help. Within this context, this article will analyse the impact of Covid-19 on the ability of victims of GBV to access justice. The first part of this article will explore the role of GBV organisations in the UK, the impact of humanitarian crises on reported rates of GBV, and how GBV can be mitigated during the Covid-19 outbreak. The second part of the article examines the effectiveness of the response to the crisis from government and public sector agencies including Her Majesty' s Courts and Tribunal Service (HMCTS), the Crown Prosecution Service (CPS) and the police. The third and final part of the article presents the findings of a UK wide study conducted by the authors into the impact of Covid-19 on GBV organisations and victims. Throughout the article, recommendations are made as to the ways in which GBV organisations could be more effectively supported to ensure justice for victims at this critical time.